Chemical composition and biological activities of rhizome and fruit rind oils of Alpinia mutica from south India. Issue 5 (2nd September 2016) - Salim, Mohamed; Rajendran, Rajesh; Ajikumaran Nair, S.; Dan, Mathew; Baby, Sabulal
Abstract: Volatile oils from dry rhizomes and fruit rinds of Alpinia mutica were isolated and characterized by GC-FID and GC-MS. A. mutica rhizome oil showed forty-seven components of which forty (92.8%) were characterized, and the major components were β-pinene (20.2%), camphor (13.3%), 1, 8-cineole (8.9%), camphene (7.9%) and α-pinene (6.2%). Fruit rind essential oil showed sixty-nine components of which sixty-three (97.8%) were identified. Major constituents in A. mutica fruit rind oil were 1, 8-cineole (14.8%), camphor (11.7%), β-pinene (7.6%) and camphene (4.8%). Four major constituents in both A. mutica rhizome and fruit rind oils (camphene, β-pinene, 1, 8-cineole, camphor) were estimated by external standardization. Refractive index, specific rotation and specific gravity of both volatile oils were determined. Fruit rind oil showed significant antioxidant, cytotoxic and moderate antimicrobial activities. A. mutica dry fruit rind oil has a very pleasant smell with potential applications in fragrances.